Cost effectiveness analysis of screening for sight threatening diabetic eye disease. Issue 7250 (17th June 2000) - James, Marilyn; Turner, David A; Broadbent, Deborah M; Vora, Jiten; Harding, Simon P
Abstract: Objective: To measure the cost effectiveness of systematic photographic screening for sight threatening diabetic eye disease compared with existing practice. Design: Cost effectiveness analysis Setting: Liverpool. Subjects: A target population of 5000 diabetic patients invited for screening. Main outcome measures: Cost effectiveness (cost per true positive) of systematic and opportunistic programmes; incremental cost effectiveness of replacing opportunistic with systematic screening. Results: Baseline prevalence of sight threatening eye disease was 14.1%. The cost effectiveness of the systematic programme was £209 (sensitivity 89%, specificity 86%, compliance 80%, annual cost £104 996) and of the opportunistic programme was £289 (combined sensitivity 63%, specificity 92%, compliance 78%, annual cost £99 981). The incremental cost effectiveness of completely replacing the opportunistic programme was £32. Absolute values of cost effectiveness were highly sensitive to varying prevalence, sensitivity and specificity, compliance, and programme size. Conclusion: Replacing existing programmes with systematic screening for diabetic eye disease is justified.